The Symbolic Capital of Ulos Amongst Christians (A Perspective of Bourdieu in Social Media Users) - Eva Solina Gultom (ELITE: Journal of English Language and Literature, 2025)
This study generally aims to describe the strategy of modern Batak and Christian sects (Charismatic churches) as the subordinate agents to achieve a recognition of their faith from Batak Toba communities who accepted Ulos and cultural practices as the symbolic capital and the cultural identity in the field of Christianity. The scope of this study focuses on the artistic field and religious identity of Batak Toba, which is depicted by reactions of Batak people who still recognize Ulos as part of the religious instrument at conventional churches, as shown in the mailing list comments, Silaban Brotherhood. This study will use ethnographic qualitative approaches and research literature. To answer this issue, Bourdieu’s perspective theory will take control of drawing identity as the mental representation of objectives toward practices committed by social agents and as the subjectivity shown by symbolic manipulation strategies. The construction of identity is produced by the existence of the power field and the occurrence of symbolic capital amongst social agents.